Occurrence of Cu and Cr in the sedimentary humic substances and pore water from a typical sugar cane cultivation area in São Paulo, Brazil - Pantano, Glaucia [UNESP]; Campanha, Mariele Barboni [UNESP]; Moreira, Altair Benedito [UNESP]; Bisinoti, Márcia Cristina [UNESP] (Springer Nature, 2013)
Purpose: The purpose of this paper is to study the interactions of sedimentary humic substances (SHS) from a sugarcane cultivation area with Cu(II) and Cr(III) and to evaluate the occurrence of these metals in the pore water and SHS. Materials and methods: For this study, the northwestern region of the State of São Paulo, Brazil, which is considered the region with the highest production of sugar cane in the state, was selected. Samples of sediment were collected from four sampling sites in the Preto, Turvo, and Grande rivers. The SHS and pore water were extracted from the sediment using the method suggested by the International Humic Substances Society and centrifugation, respectively. The complexing capacity (CC) of the SHS for Cu(II) and Cr(III) was determined by individually titrating these metals with an ultrafiltration system using tangential flow. The total concentrations of Cr and Cu were determined for the pore water, sediments, and humic substances with graphite furnace atomic absorption spectrometry and Zeeman background correction after an acid digestion, according to the methods described in US EPA Method 3050B. Results and discussion: The SHS from a site in the Turvo River, which is typically cultivated with sugarcane, possessed the highest concentration of Cu bound to SHS (25.0%), the largest CC (0.63 mmol Cu g-1 HS) and the highest concentration of this metal in the pore water (1.38 mg Cu Kg-1 sed.). For Cr, the SHS collected from a location on the Preto River dam had the largest CC (0.90 mmol Cr g-1 HS) and the lowest Cr content in the pore water (0.29 mg Cr Kg-1 sed.), indicating that there was an inverse relationship between the CC and the concentration of metal available in the pore water. Conclusions: Sedimentary humic substances might be one of the regulatory factors controlling the availability of Cu and Cr in the sediments found in a typical region that has been planted with sugarcane. Distinct behaviors were observed between the two elements investigated; higher CC and a larger fraction of Cu(II) were found in the pore water of samples originating from sugarcane crops. The opposite behavior was observed for the Cr(III) species. © 2013 Springer-Verlag Berlin Heidelberg.
Keywords: Complexing capacity; Pore water; Sediment; Sedimentary humic substance